2001
DOI: 10.1097/00005392-200109000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Radical Cystectomy Is Safe in Elderly Patients at High Risk

Abstract: Our results support the safety of radical cystectomy in elderly patients at high risk. Acceptable perioperative morbidity and mortality may be achieved without routine intensive monitoring postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
9

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 14 publications
3
31
0
9
Order By: Relevance
“…In elderly patients as well, several investigators have shown that radical cystectomy could be safely performed with acceptable perioperative morbidity and mortality, if candidates for this aggressive surgery were properly selected [8][9][10][11][12][13][14][15][16][17][18]. However, there are some problems in these studies that remain to be elucidated as follows: (1) The definition of elderly has varied in each study, and there are only six series analyzing patients aged ‡80 years undergoing radical cystectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In elderly patients as well, several investigators have shown that radical cystectomy could be safely performed with acceptable perioperative morbidity and mortality, if candidates for this aggressive surgery were properly selected [8][9][10][11][12][13][14][15][16][17][18]. However, there are some problems in these studies that remain to be elucidated as follows: (1) The definition of elderly has varied in each study, and there are only six series analyzing patients aged ‡80 years undergoing radical cystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the previous studies, patients aged ‡70 or 75 years were defined as elderly [8][9][10][11][12]; however, in this series, we defined elderly patients as those aged ‡80 years in order to more specifically characterize the features of elderly patients treated with radical cystectomy and urinary diversion. Using this criterion, there were 72 elderly patients among 629 patients undergoing radical cystectomy at our institutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intensive chest physiotherapy, bronchodilators, effective bowel preparation with intravenous fluids to avoid dehydration, expeditious surgery with careful attention to surgical technique, intensive monitoring and early mobilization of the patient are some of the measure that have been helpful in avoiding complications in our patients. In a selected group of high-risk patients, admission to intensive care units for additional evaluation and monitoring may be indicated [8,24]. No routine use of digitalis [9,10,25] or anticoagulation [10,24,25] as advocated by few were done.…”
Section: Discussionmentioning
confidence: 99%
“…Während es in 3 dieser Serien [20,21,22] zu keinen Todesfällen kam, starben in den beiden anderen Serien [23,24] [20,28]. Die Rate an Spätkomplikationen variierte in den genannten 5 Serien zwischen 6 und 52% [20,21,22,23,24]. Hier standen chirurgische Komplikationen im Vordergrund, wobei eine Ileussymptomatik, Narbenhernien und Inkontinenz nach Blasenersatz am häufigsten waren.…”
Section: Mortalitätunclassified